Peningkatan Hasil Belajar Siswa Menggunakan Model Problem-based Learning Berbantuan Android-based Packet Tracer - Anik Nor Hidayah; Basori Basori; Astika Wulansari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2022)
Student learning outcomes are closely related to the learning strategies applied by the teacher. Many teachers still teach in improvised ways so that student achievement becomes low. This study aims to determine the improvement of learning outcomes in the subject of Network Infrastructure Administration for class XI TKJ 2 SMKN 1 Boyolali using a problem-based learning (PBL) model with the help of an Android-based packet tracer. This study uses a classroom action research method with two cycles where each cycle uses two meetings and begins with the planning stage, implementation stage, observation, and reflection stage. Researchers took the subject of students XI. Data was obtained through documentation and theoretical testing. Data analysis with descriptive analysis. The results showed that in the initial state or pre-cycle using the discovery learning model, student learning completeness only reached a percentage of 41%. Cycles 1 and 2 were carried out using an Android-based PBL model assisted by a packet tracer. In cycle 1, learning completeness increased by 51%, and in cycle two by 81%. These results can be concluded that the PBL model assisted by an Android-based packet tracer which is a modification of the PBL model, is very feasible to be applied to learning in Network Infrastructure Administration.